Urbanization in Developing Countries - Vernon Henderson (World Bank, 2013)
The rapid urbanization in many developing countries over the past half century seems to have been accompanied by excessively high levels of concentration of the urban population in very large cities. Some degree of urban concentration may be desirable initially to reduce inter- and intraregional infrastructure expenditures. But in a mature system of cities, economic activity is more spread out. Standardized manufacturing production tends to be de-concentrated into smaller and medium-size metropolitan areas, whereas production in large metropolitan areas focuses on services, research and development, and non-standardized manufacturing. The costs of excessive concentration (traffic accidents, health costs from exposure to high levels of air and water pollution, and time lost to long commutes) stem from the large size of megacities and underdeveloped institutions and human resources for urban planning and management. Alleviating excessively high urban concentration requires investments in interregional transport and telecommunications to facilitate de-concentration of industry. It also requires fiscal de-concentration, so that interior cities can raise the fiscal resources and provide the services needed to compete with primate cities for industry and population.